Creative Teaching Practices: A Combination of Total Physical Response (TPR) at Elementary School Students in Tangerang - Eva Agistiawati; Aris Fuadi; Siti Mariyanah (Niswantara: Jurnal Pengabdian Kepada Masyarakat, 2025)
Teaching English as a foreign language is not easy, especially teaching English to elementary students. Teachers are expected to always have creative and innovative ideas to attract students' attention in classroom teaching activities so that students can understand the material being taught. Total Physical Response (TPR) is one method that can be applied. TPR is a method that uses body movements to interpret words. The purpose of holding training using this method is to help teachers teach English and create a pleasant classroom atmosphere. This method is easy to apply to teachers at MIN 1 Tangerang. The participants who attended were 48 people consisting of the Principal and teachers. The methods used include 1) providing material about TPR regarding theory and examples with power points and videos, 2) assigning participants in groups to find themes and practice TPR, 3) guidance and discussion about the TPR that was practiced. The results of this activity were that all participants were enthusiastic and could use the TPR method well.